2019
DOI: 10.1155/2019/3807207
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Evaluation, Embryotoxicity, and Teratogenic Effects of Curcuma longa Extract on Zebrafish (Danio rerio)

Abstract: Curcuma longa L. is a rhizome plant often used as traditional medicinal preparations in Southeast Asia. The dried powder is commonly known as cure-all herbal medicine with a wider spectrum of pharmaceutical activities. In spite of the widely reported therapeutic applications of C. longa, research on its safety and teratogenic effects on zebrafish embryos and larvae is still limited. Hence, this research aimed to assess the toxicity of C. longa extract on zebrafish. Using a reflux flask, methanol extract of C. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 45 publications
4
50
0
2
Order By: Relevance
“…This corresponds to the previous finding on Curcuma longa Linn. extract which exhibited embryotoxicity at high concentrations (125 µg/mL) on developing zebrafish [14]. The zebrafish fed with the essential oil from Pistacia lentiscus Var.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to the previous finding on Curcuma longa Linn. extract which exhibited embryotoxicity at high concentrations (125 µg/mL) on developing zebrafish [14]. The zebrafish fed with the essential oil from Pistacia lentiscus Var.…”
Section: Discussionmentioning
confidence: 99%
“…extract using a zebrafish model are reported. [14]. Thus, the current investigation was used the zebrafish embryo model to assessment the embryotoxicity and teratogenicity of essential oil from Z. cassumunar.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal plants have pharmacological and therapeutic characteristics due to the natural chemical compounds they contain [ 1 ]. Hence, they are widely utilized every day for culinary purposes and nutritional supplements to promote health [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds in medicinal plants can have toxic impacts on cardiac glycosides, phorbol esters, alkaloids, cyanogenic glycosides, and lectins [ 10 ]. The statistical evaluation carried out by the National Pharmaceutical Control Bureau and Health ministry’s Malaysian Adverse Drug Reaction Advisory Committee in 2013 confirmed that 11,437 cases of harmful drug reaction had been reported, and 0.2% were due to herbal remedies [ 1 ]. Thus, the evaluation of the toxicity of potential drug compounds has been enhanced in recent years [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation